Contribution of the Caspase Gene Sequence Diversification to the Specifically Antiviral Defense in Invertebrate - Zhi, Bin (Public Library of Science, 2011)
Vertebrates achieve adaptive immunity of all sorts against pathogens through the diversification of antibodies. However the mechanism of invertebrates' innate immune defense against various pathogens remains largely unknown. Our study used shrimp and white spot syndrome virus (WSSV) to show that PjCaspase, a caspase gene of shrimp that is crucial in apoptosis, possessed gene sequence diversity. At present, the role of gene sequence diversity in immunity has not been characterized. To address this issue, we compared the PjCaspase gene sequence diversities from WSSV-free and WSSV-resistant shrimp. The sequence analysis indicated that the PjCaspase gene from the WSSV-resistant shrimp contained a special fragment, designated as fragment 3 (221–229 aa). Down-regulation or overexpression of the PjCaspase gene containing fragment 3 led to significant inhibition or enhancement of virus-induced apoptosis, but had no effect on bacterium challenge. We found evidence that the silencing or overexpression of this gene led to a 7-fold increase or 11-fold decrease of WSSV copies, respectively. Our results suggested that the PjCaspase gene containing fragment 3 provided the molecular basis for the antiviral defense of shrimp. This study represented the first report of the role of gene sequence diversity in the immunity of an invertebrate against virus infection. Invertebrates may employ this gene sequence diversity as a system to avoid pathogen interference with their immune response.